Asymmetric syntheses, ring opening and stereoselective reactions, absolute conformation and activation barrier determinations on axially chiral oxazolidine derivatives - Ordu, Öznur Demir. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2008., 2008)
In this study, sterically hindered 5-methyl-3-(o-aryl)-2,4-oxazolidinediones, 5-methyl- 3-(o-iodophenyl)-2-thioxo-4-oxazolidinedione and 5,5-dimethyl-3-(o-aryl)-2,4- oxazolidinediones have been synthesized. Diastereomeric isomers of the 5-methyl-3-(oaryl)- 2,4-oxazolidinediones and 5-methyl-3-(o-iodophenyl)-2-thioxo-4-oxazolidinedione and enantiomeric isomers of the 5,5-dimethyl-3-(o-aryl)-2,4-oxazolidinediones have been identified by 1H NMR and 13C NMR. Activation barriers to hindered rotation around C-N single bond have been determined by using temperature dependent NMR or by thermal racemization on chiral sorbents by HPLC. The conformational preferences of the diastereomers have been investigated by one and two dimensional NMR spectroscopy and by HPLC on an optically active sorbent. It was found that when the bulky group on C-5 and the ortho substituent on the aromatic ring are on opposite sites the conformation becomes more stable. Absolute confomations of 5,5-dimethyl-3-(o-aryl)-2,4-oxazolidinediones have been determined by one and two dimensional 1H NMR in the presence of a chiral auxiliary (S)- (+)-1-(9-anthryl)-2,2,2-trifluoro ethanol ((S)-TFAE). A solvation model has been proposed for the determination absolute stereochemistry on the basis of interactions between the enantiomers and (S)-TFAE. vi Asymmetric alkylation and aldol reactions have been carried out on 5-methyl-3-(otolyl)- 2,4-oxazolidinedione, 5-methyl-3-(o-iodophenyl)-2,4-oxazolidinedione and 5- methyl-3-(o-iodophenyl)-2-thioxo-4-oxazolidinedione over the lithium enolate forms. The enolate formation could be achieved by lithium diisopropylamide at -78 0C under nitrogen. It was found that the o-aryl substituents had a stereodirecting effect on the reactions taking place at C-5 of the ring. The stereoselectivity of the reactions was determined by using chiral HPLC. Basic and reductive ring opening reactions of diastereomeric 5S-methyl-N-(o-aryl)- 2,4-oxazolidinediones and enantiomeric 5,5-dimethyl-N-(o-aryl)-2,4-oxazolidinediones have been done to examine the stability of the ring and to synthesize various organic compounds such as chiral –hydroxyamides, carbamoyloxyacids and carbamate derivatives via ring opening. It was observed that 5-methyl-2,4-oxazolidinedione ring cleaved more easily than 5,5-dimethyl-2,4-oxazolidinedione ring. 5-Methyl-2,4- oxazolidinedione ring was reduced to a primary alcohol after ring opening, whereas the reduction of 5,5-dimethyl-2,4-oxazolidinedione ring yielded a secondary alcohol asymmetrically without ring cleavage.
Keywords: Chirality.; Stereochemistry.; Enantiomers.; Asymmetric synthesis.; Ring-opening polymerization.